2020
DOI: 10.1021/acsaem.0c01823
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Cation-Substituted Na3SbS4 Solid Electrolytes

Abstract: To realize all-solid-state sodium-ion batteries, the ionic conductivities and stabilities of solid electrolytes must be improved. The sulfide Na 3 SbS 4 electrolyte is known to show a high sodium-ion conductivity of over 10 −3 S cm −1 at room temperature. In this study, cation-substituted Na 3 SbS 4 solid electrolytes with excess Na or Na vacancies were prepared, and the effects of substitution on the material conductivity were examined. The ionic conductivities of the Na 3+x Sb 1−x M x S 4 (M = Si, Ge, Sn) el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 26 publications
0
24
0
Order By: Relevance
“…At the same time, the Na3PS4 structural archetype has proven to be a fertile playground for materials design through elemental substitutions, defining a wider materials family of the general composition Na3PnCh4 (Pn: pnictogens P, As, Sb; Ch: chalcogens S, Se) 16,17,[26][27][28][29][30][18][19][20][21][22][23][24][25] ; receptive to various aliovalent substitutions, e.g. Ca 2+ on the sodium sites 31 , Clon the chalcogenide site i [32][33][34][35] , and Si 4+ or W 6+ on the pnictide site [36][37][38][39][40][41][42][43][44] . Notable compositions of the Na3PS4 structural family include Na3SbS4 with a room-temperature conductivity of the order of 10 -3 S/cm and distinct stability against ambient moisture 20,21,30 , and the recently reported tungsten-doped Na3-xWxSb1-xS4 with room-temperature Na + -conductivity of the order of 10 -2 S/cm 39,40 , currently the highest reported among polycrystalline Na + and Li + conductors.…”
mentioning
confidence: 99%
“…At the same time, the Na3PS4 structural archetype has proven to be a fertile playground for materials design through elemental substitutions, defining a wider materials family of the general composition Na3PnCh4 (Pn: pnictogens P, As, Sb; Ch: chalcogens S, Se) 16,17,[26][27][28][29][30][18][19][20][21][22][23][24][25] ; receptive to various aliovalent substitutions, e.g. Ca 2+ on the sodium sites 31 , Clon the chalcogenide site i [32][33][34][35] , and Si 4+ or W 6+ on the pnictide site [36][37][38][39][40][41][42][43][44] . Notable compositions of the Na3PS4 structural family include Na3SbS4 with a room-temperature conductivity of the order of 10 -3 S/cm and distinct stability against ambient moisture 20,21,30 , and the recently reported tungsten-doped Na3-xWxSb1-xS4 with room-temperature Na + -conductivity of the order of 10 -2 S/cm 39,40 , currently the highest reported among polycrystalline Na + and Li + conductors.…”
mentioning
confidence: 99%
“…[ 147,148 ] When comparing solid‐state synthetic approaches and ball milling, it was shown that Mo can be introduced in Na 3 SbS 4 using mechanochemical milling, whereas a solid‐state synthesis does not lead to a Mo incorporation, suggesting that milling does have an additional influence on the phase stability of these highly substituted materials. [ 147,149 ] A different type of disorder of sodium within the structure, where the compound still resembles the nominal composition, but has partially vacant sodium positions, with interstitial positions being slightly occupied by the missing sodium is discussed in a theoretical work by Zhu et al, [ 143 ] where it is shown that this type of disorder significantly boosts the electrochemical performance. This general idea of introducing disorder in the mobile species substructure might be the reason, why the mechanochemically synthesized compounds usually have a better ionic conductivity, as it has been previously reported for different materials.…”
Section: The Beneficial or Detrimental Influence Of Mechanochemistry In Solid Electrolytesmentioning
confidence: 99%
“…Similar with Na 3 PS 4 conductor, Na 3 SbS 4 also displays polymorphs that include tetragonal structure ( F 43 m space group) at room temperature and cubic structure ( P 421 c space group) at elevated temperatures [17,18] . There are many studies on the Na 3 SbS 4 family conductors regarding the interface stability against Na metal, [19–22] doping chemistry (i. e., W, Ge, Cl, Se), [23–26] and electrochemical performance [27,28] . When S is partially replaced by a large anion such as Se, Na 3 SbS 4‐ x Se x conductors show changes in the crystal structure from tetragonal Na 3 SbS 4 to cubic Na 3 SbSe 4 at room temperature [29] .…”
Section: Figurementioning
confidence: 99%